Cœur, Temps and Monde in Le forçat innocent of Supervielle: A Poet’s Existential Metaphors of Prison and Shelter - Franck Dalmas (Studies in 20th & 21st Century Literature, 2009)
Poet Jules Supervielle has a marginal status in twentieth-century French literature as he was not engaged in any prominent movement of his time (Symbolism, Futurism, or Surrealism). In that regard, his poetry is neither nationally colored nor aesthetically connoted. It might well be the reason for his lacking consideration in the literary canon. But these differences must get our special attention. Supervielle was not born in France and he was to live and write his works in a state of existential angst, divided, as he always felt, between his native Uruguay and his French legacy. As such, the poet developed a unique intimate oeuvre through which he tried to recapture and mingle his vacant identities. This article examines the recurrent themes of “heart,” “time,” and “world” in the collection of poems Le forçat innocent (1930) to show that a life-long meditation on his defective health, the unmanageable flow of time, and the hope for universal communion helped Supervielle overcome these metaphorical prisons and create a propitious shelter to his poetic expression. Contrasting aspects in his poetry, however, cannot stand apart from each other, and we have to consider their interlacing, which illuminates Supervielle’s work in a truly phenomenological manner.
Keywords: poet; Jules Supervielle; Uruguay; France; French; identity; heart; time; world; Le forçat innocent; flow of time; health; prison; shelter; existential metaphor